Derivatization following hollow‐fiber microextraction with tetramethylammonium acetate as a dual‐function reagent for the determination of benzoic acid and sorbic acid by GC. Issue 14 (21st June 2013) - Sun, Yang; Wang, Xiaoqing; Huang, Yilei; Pan, Zaifa; Wang, Lili
<x xml:space="preserve">Abstract</x> Derivatization at the injection port following hollow‐fiber‐based liquid–liquid–liquid microextraction with tetramethylammonium acetate as a dual‐function reagent, i.e. an acceptor and derivatization reagent, for the determination of benzoic acid (BA) and sorbic acid (SA) in real samples by GC was developed. BA and SA were extracted from aqueous samples to an organic phase impregnated into the pores of the hollow fiber wall, and then back‐extracted to the acceptor solution located inside the lumen of the hollow fiber. Upon injection, the extracted analytes were quantitatively derivatized to their methyl esters with tetramethylammonium acetate in the GC injection port. Several parameters related to the derivatization and extraction efficiency were optimized. The linearity was satisfactory over a concentration range of 0.1–50 mg/L with r > 0.993 for both analytes. The LODs were 2.0 μg/L for SA and 20 μg/L for BA. The recoveries (83–116%) and precisions (RSDs of 1.2–11.4% (n = 3)) were examined by analyzing real spiked samples. The enrichment factors of BA and SA were 300 and 425. The results demonstrated that this is a simple, rapid, accurate, and sensitive method for the determination of BA and SA in various samples.